Latest Criminalistic Tools and Technologies in the Investigation of Cybercrimes: International and Ukrainian Experience - Shevchuk, Viktor; Bululukov, Oleg; Chornyi, Hennadii; Tyshchenko, Olha; Baranchuk, Vasyl (Law, State and Telecommunications Review, 2025)
[Purpose] The purpose of this study was to examine promising technologies for investigating cybercrime based on international experience. [Methodology/approach/design] The study employed comparative legal analysis to assess various legal systems and practices, focusing on the integration of specialized knowledge in cybercrime investigations, with particular attention to European countries. [Findings] The findings highlight the growing role of automation, digitalization, and artificial intelligence (AI) in enhancing the efficiency of criminal investigations. These technologies are increasingly used in the pre-trial and court processes, improving the effectiveness of detecting, investigating, and preventing cybercrimes. The study emphasizes the transnational nature of cybercrime and the importance of international cooperation in addressing the challenges posed by the digital environment. The use of criminalistic tools, such as EnCase™ Forensic, AccessData FTK Imager, and IBM i2 Analyst’s Notebook, has proven critical in advancing forensic science, particularly in the collection and analysis of digital evidence. Despite challenges, including martial law and limited resources in Ukraine, the study advocates for the adaptation of international best practices to improve the country’s cybersecurity framework. [Practical implications] Such a comprehensive approach to these issues ensures the efficiency and effectiveness of criminal justice tasks, considering international standards and the Ukrainian reality of the current military situation.